Correlation of free T4 level at diagnosis and 03, 06 months after fixed dose radioiodine therapy among the hyperthyroid patients - Sanooz Raheem (Sri Lanka Journal of Diabetes Endocrinology and Metabolism, 2020)
Our study aimed to identify the correlation between the presenting FT4 values and FT4 values after the radioiodine therapy. Patients, after 10 mCi fixed dose radioiodine therapy for thyrotoxicosis were followed up at 03, 06 months intervals at Nuclear Medicine, Peradeniya. The details on base line clinical presentation, FT4 levels and the clinical status after the radioiodine therapy were collected using an interviewer administered questionnaire. Data was analysed using the SPSS version 25 by using Pearson’s correlation and independent sample t-test. There were 70.2% of Graves’ disease patients and 29.8% of toxic multi nodular goitre patients among the 57 patients consented for the follow up. The Pearson’s correlation showed a weak relationship between the FT4 value on diagnosis and the FT4 value after 03 months (r=0.475, P0.003) and a moderate relationship between the presenting FT4 value and the FT4 value before any intervention on or before 06 months after the radioiodine therapy (r=0.644, P<0.001). Before any intervention on or before 06 months from radioiodine therapy patients who were hyperthyroid had high mean FT4 value on diagnosis compared to euthyroid or hypothyroid patients (P0.009). This study has found a correlation between the FT4 value on diagnosis and the FT4 value before any intervention on or before 06 months after radioiodine therapy and the FT4 level on diagnosis can be used as a predictor for the outcome of radioiodine therapy.